The Psychology of Death in The Perspective of Islamic Eschatology - Yati Khalala; Farhatina Kamila; Mahfudz Badawi; Sefiani Putri Sakila; Rama Galih Manunggal; Veni Valentina (International Tatho Academics, 2025)
The fears and anxieties that arise regarding death often plague the human mind. This paper aims to identify the concept of the psychology of death according to Komaruddin Hidayat to help humans face death. This research uses a descriptive qualitative approach by observing YouTube videos that discuss Komarudin Hidayat's ideas on the psychology of death and Islamic spiritual values. Komarudin Hidayat stated that death is the beginning of eternal life in Islam, encouraging physical and mental preparation. Insan kamil is able to control the worldly and spiritual and draw closer to God. The psychology of death views it as part of the spiritual journey towards the Divine. The study of Komarudin Hidayat's psychology of death shows that an understanding of death can affect individual behavior and attitudes, making it important to understand the concept of death in the context of psychology. This study contributes to the development of spiritual psychology by highlighting the importance of integrating psychological understanding of death with religious values in Islamic society.